Characterization of the biological clock in Svalbard ptarmigan (Lagopus muta hyperborea) - Hofinger, Anna Malena (UiT Norges arktiske universitet, 2021)
Svalbard ptarmigan (Lagopus muta hyperborea), permanent inhabitants of the High Arctic, lose daily behavioral rhythmicity during polar day and night, and rhythms in core body temperature (Tb) weaken after prolonged exposure to constant photic conditions. A weak circadian system has been suggested in Svalbard ptarmigan, however, the molecular clockwork in Svalbard ptarmigan has not been investigated yet. Here, we studied activity and Tb in Svalbard ptarmigan after controlled changes in light conditions and examined the molecular dynamics of the clock. We show that daily rhythms in locomotor and feeding activity in Svalbard ptarmigan stop after a transition from external light-dark cycles (LD) to constant dark (DD)/constant light (LL), while rhythms in Tb persisted for at least 10 days in all experimental birds. Approximately four days after a transition from DD to LD birds showed a rise in Tb in anticipation of light onset. These findings suggest an endogenous timing system in control of Tb under LD that weakens under constant conditions. A sustained ultradian rhythmicity was present during the entire experimental design, however, the underlying mechanisms driving ultradian rhythms in Svalbard ptarmigan remain unclear. To investigate the molecular dynamics of the clock we performed luciferase promoter reporter assays and qPCRs with Svalbard ptarmigan skin fibroblasts. We observed daily oscillations in Per2 and Bmal1 transcription, however, no rhythmicity in clock gene expression was measured by qPCRs. This discrepancy may reflect the high temperature sensitivity of our promoter reporters to small temperature fluctuations we detected in our equipment. Finally, we show that ptarmigan fibroblasts cycle with simulated body temperature cycles with Per1 and Bmal1 transcription being in phase, indicating a response to temperature cycles rather than to an endogenous clock. Taken together, these findings argue for a weak circadian system in Svalbard ptarmigan.